2006
DOI: 10.2118/06-01-04
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Oxidation Behaviour of Pure Hydrocarbon Components and Crude Oils Utilizing PDSC Thermal Technique

Abstract: High Pressure Air Injection (HPAI) is an Improved Oil Recovery (IOR) technique in which compressed air is injected into light oil, high-pressure reservoirs. The objective of this process is the oxygen from the injected air reacts with a small fraction of the reservoir oil at an elevated temperature to produce a mixture of carbon dioxide and nitrogen. The produced gas flowing from the reaction region mobilizes the oil downstream of the reaction zone towards the production wells. Knowledge of the oil's oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 0 publications
6
40
1
Order By: Relevance
“…In the HTO regions, a decrease in the peak temperature of exothermic activities was observed. Similar observations were reported by Li et al [15] in their own DSC studies. Based on DSC results and operation conditions in this numerical simulation study (temperature range: 75-150°C, pressure 210 psi), pressure seems to have a minor effect in LTO reaction.…”
Section: Pressure Effect In Lto Reactionsupporting
confidence: 92%
“…In the HTO regions, a decrease in the peak temperature of exothermic activities was observed. Similar observations were reported by Li et al [15] in their own DSC studies. Based on DSC results and operation conditions in this numerical simulation study (temperature range: 75-150°C, pressure 210 psi), pressure seems to have a minor effect in LTO reaction.…”
Section: Pressure Effect In Lto Reactionsupporting
confidence: 92%
“…An improved LTO model and simplified reaction pathways were developed to bring about mechanism understanding of oil oxidation in depth. The oxidation characteristic of three crude oils was examined by Li et al (2006) using pressure differential scanning calorimeter (PDSC) test and the results indicated that the oxidation extent was highly dependent on oil chemical compositions. Zhang et al (2014)and Niu et al (2011) took advantage of static oxidation reactor to characterize the LTO behaviors of crude oils with different API gravity.…”
Section: Introductionmentioning
confidence: 99%
“…-Saffar et al, 2001;Li et al, 2004Li et al, , 2006. Due to the excess evaporation of light oil, FD stage (450°C -470°C) is poor because of less LTO residue available which can convert into fuel (coke) during LTO.…”
Section: Methodsmentioning
confidence: 99%